Parasites, Zoonoses and War A Themed Issue in Honor of Emeritus Professor John M Goldsmid - Bradbury, Richard S. (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This book is a collection of chapters around the theme of parasitology and zoonosis in bot war and peace and the impact of these fields on public health. Individual experts have contributed reviews, novel research, and case series within the field to make a broad and interesting collection designed to stimulate thought and discussion in this area. The collection is dedicated to the life and career of Emeritus Professor John Marsden Goldsmid, an eminent parasitologist and advocate for further attention to these above listed fields of medicine. It would be suitable for medical and veterinary practitioners, students, scientists, and epidemiologists with an interest in parasitology and public health.